Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
D)
[tex]an = -6 \times {( \frac{1}{4} )}^{n - 1} [/tex]
Step-by-step explanation:
(See the picture)
The explicit formula is given as [tex]T_n=-6(\frac{1}{4} )^{n-1}[/tex]
Geometric and recursive functions
The general explicit formula for a geometric sequence is expressed as:
- [tex]T_n=ar^{n-1}[/tex]
Given the following recursive functions:
[tex]a_1=-6\\ a_n=a_{n-1}\cdot\frac{1}{4} [/tex]
Get the next two terms:
[tex]a_2=a_{1}\cdot\frac{1}{4} \\ a_2=-6\cdot\frac{1}{4} \\ a_2=\frac{-3}{2} [/tex]
For the third term:
[tex]a_3=a_{2}\cdot\frac{1}{4} \\ a_3=\frac{-3}{2} \cdot\frac{1}{4} \\ a_3=\frac{-3}{8} [/tex]
The common ratio for the sequence will be [tex]\frac{1}{4} [/tex]
The explicit formula is given as [tex]T_n=-6(\frac{1}{4} )^{n-1}[/tex]
Learn more on explicit functions here: https://brainly.com/question/10308651
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.